Highlighting the Treatment Regimens used in COVID-19 epidemic in Iraq with Special Regards to Vitamin D - AL-Nema, Zinah Mudhafar; Natiq Yahya, Ruaa; Mubdir Khalf, Noor (Iraqi Journal of Pharmaceutical Sciences, 2022)
Coronavirus disease 2019 (COVID-19) is a flu-like infection caused by a novel virus known as Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2). After the widespread around the world, it was announced by the World Health Organization (WHO) as a global pandemic. The symptoms of COVID-19 may arise within 2 weeks and the severity ranged from mild with signs of respiratory infection to severe cases of organ failure and even death. Management of COVID-19 patients includes supportive treatment and pharmacological medications expected to be effective with no definitive cure of the disease. The aims of this study are highlighting the management protocol and supportive therapy especially vitamin D and manifesting the clinical symptoms by patients in Iraq. An observational study was conducted on 200 patients and descriptive parameters for data were calculated to analyze the results. The mean age was 42.56±17.49 years and the majority of patients were presented with mild to moderate symptoms (78%). There were many different pharmacological treatment regimens and random doses and duration of vitamin D were taken by the patients. In conclusion, a non-specific treatment protocol was used for the patients without compliance to the national guidelines for management and treatment of COVID-19 patients in Iraq with the administration of a wide range of pharmaceutical agents that required monitoring for their safety and efficacy. Vitamin D is administered in different doses and duration without depending on the basal serum concentration.